2020
DOI: 10.1097/bpo.0000000000001587
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Growth Quantitatively Through Proximal Tibia Radiograph Markers

Abstract: Background: The creation of accurate markers for skeletal maturity has been of significant interest to orthopaedic surgeons. They guide the management of diverse disorders such as adolescent idiopathic scoliosis, leg length discrepancy, cruciate ligament injuries, and slipped capital femoral epiphysis. Multiple systems have been described to predict growth using radiographic skeletal markers; however, no such system has yet been developed for the proximal tibia. The purpose of this study was to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…We also utilized the first post-treatment radiographs performed within 2 weeks of surgery which provided more standardized imaging on which to perform our skeletal maturity assessments. Third, the Kahan formula utilized in this study to estimate GRP was derived from the Bolton Brush study, which was sourced in 1926 from predominantly white children from wealthy families 13,16 . As such, while prior studies have demonstrated the Brush cohort has matched well to a modern cohort, it is possible that this influences generalizability in our predominantly Black and more socioeconomically diverse cohort 11 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We also utilized the first post-treatment radiographs performed within 2 weeks of surgery which provided more standardized imaging on which to perform our skeletal maturity assessments. Third, the Kahan formula utilized in this study to estimate GRP was derived from the Bolton Brush study, which was sourced in 1926 from predominantly white children from wealthy families 13,16 . As such, while prior studies have demonstrated the Brush cohort has matched well to a modern cohort, it is possible that this influences generalizability in our predominantly Black and more socioeconomically diverse cohort 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Two maturity markers capable of being generated exclusively from knee radiographs were identified. Kahan and colleagues developed a system for predicting skeletal maturity based on measurements of the regional physes of the knee which was derived from a study cohort of primarily adolescents 13,16–19 . Their growth remaining percentage (GRP) was calculated using the following formula:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations